Perceived Behavior Control in Diabetic Patients: A Conceptual Analysis - Nurul Wana; Shinta Nur Cahyanti; Satriya Pranata; M. Fatkhul Mubin (CV. Publikasi Indonesia, 2026)
Diabetes mellitus is a chronic metabolic disease that requires long-term self-management and sustainable treatment efforts to prevent complications, reduce the risk of morbidity, and improve the patient's quality of life. One of the important psychosocial concepts in diabetes management is Perceived Behavior Control (PBC), which is an individual's perception of one's ability to control health behaviors related to glycemic control, decision-making, and problem-solving. The analysis of this concept was carried out through a review of the latest literature on the determinants of PBC. The results of the analysis showed that PBC was influenced by internal and external factors such as knowledge, psychological conditions, family and health worker support, health insurance, culture and spirituality, communication, clinical conditions, and self-efficacy. PBC plays a major role in the success of patients managing their diet, engaging in physical activity, adhering to medication, monitoring glucose levels, and overcoming barriers in self-management. The consequences of good PBC include increased healthy behaviors, decreased complications, improved quality of life, and decreased health care costs. Thus, a deep understanding of PBC is essential to develop effective self-management interventions for diabetic patients.